Rekonsepsi Pendidikan Karakter Berbasis Islam Pada Masyarakat Multikultural Singapura - Haris, Abd.; Ramadhan, Salman Arif; Mubarok, Leufigo Sadam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Inequality that occurs in this life is caused by poor human character. Efforts to equip generations with character education continue to be a concern. The purpose of this research is to reveal; (1) the form of reconceptualization of Islamic-based character education in the Singapore Perdaus institution, (2) the influencing factors, and (3) the impact or implications. The approach used is qualitative, the research data is information about character education in the Perdaus Singapore institution, the data analysis is descriptive-qualitative. The findings of this study are (1) the concept of character education in the Singapore Perdaus institution is implemented in the form of character education through the al-Quran, kurban activities, early childhood education, and character education for youth, (2) there are two influencing factors, namely; External factors include government support, public awareness, well-established community conditions, and high intensity of career women. As for the internal factors in the form of competent human resources, open institutions, and innovation and adequate facilities, (3) the positive impact is the strengthening of public trust in Islamic institutions, the birth of a cultured generation of advanced society, and the opening of job opportunities. The conclusion of this study shows that the values of universal Islamic character do not conflict with the life of developed societies.